(untitled) (Journal of Ideas in Health, 2022)
Background: Human cytomegalovirus (HCMV) seroprevalence is a significant health problem, especially among pregnant women in lower socioeconomic societies. This study aims to explore the prevalence of HCMV infections among women in Iraq. Methods: A systematic review was designed to collect and summarize articles concerning the relationship between HCMV infection and abortion in Iraq. We identified the titles and abstracts of the publications from 2008 to 2022. A pre-defined keyword was recruited to recognize the publications and filter the articles to eliminate duplication and remove irrelevant articles. In the reviewed studies, the HCMV was detected using diagnostic methods such as enzyme-linked immunosorbent assay and immunochromatography (rapid test) or molecular methods such as polymerase chain reaction. Results: Twenty-four eligible articles have been included in this review sourced data from about 5442 patients covering 15 of 18 provinces in Iraq. The prevalence of HCMV IgG and IgM was (0%-100%) and (0%-93%), respectively. Many factors influenced the varied results, including the design of the study and sociodemographic and clinical aspects. Conclusion: The high prevalence of HCMV infection indicates a causative relationship with repeated abortion among Iraqi females.